2014
DOI: 10.1016/j.ejphar.2013.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of fatty acid amide ligands in activating and desensitizing G protein-coupled receptor 119

Abstract: The purpose of the current study was to apply a high throughput assay to investigate the structure-activity relationships of fatty acid amides for activating and desensitizing G protein-coupled receptor 119, a promising therapeutic target for both type 2 diabetes and obesity. A cell-based, homogenous time resolved fluorescence (HTRF) method for measuring G protein-coupled receptor 119-mediated increase of cyclic adenosine monophosphate (cAMP) levels was validated and applied in this study. Using novel fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(43 reference statements)
0
5
0
1
Order By: Relevance
“…Additionally, the kinetics of the calcium response and levels of receptor reserve may also contribute to the observed differences in desensitization profile between these systems. A second recent report suggested that both AR-231,453 and oleoylethanolamide evoke complete desensitization of GPR119 cAMP responses (Kumar et al, 2014). However, in these experiments the investigators did not appear to wash out excess ligand before challenging with a second stimulus, which may preclude the observation of re-stimulation responses and therefore confound the observation of true desensitization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, the kinetics of the calcium response and levels of receptor reserve may also contribute to the observed differences in desensitization profile between these systems. A second recent report suggested that both AR-231,453 and oleoylethanolamide evoke complete desensitization of GPR119 cAMP responses (Kumar et al, 2014). However, in these experiments the investigators did not appear to wash out excess ligand before challenging with a second stimulus, which may preclude the observation of re-stimulation responses and therefore confound the observation of true desensitization.…”
Section: Discussionmentioning
confidence: 96%
“…Functionally, the consequences of this mechanism have been defined as sustained receptor activation even after removal of excess agonist (Calebiro et al, 2009;Ferrandon et al, 2009;Haskell-Luevano et al, 1996;Mullershausen et al, 2009). Whilst some evidence for GPR119 desensitization has been previously reported (Kumar et al, 2014;Lauffer et al, 2009;Zhang et al, 2014), a comprehensive characterization of desensitization of GPR119 cAMP signalling has not yet been conducted. This key gap in our understanding of GPR119 biology may be especially pertinent to observations of tachyphylaxis and lack of efficacy of GPR119 agonists in the clinic (Kang, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…These 14 known GPR119 agonists were selected from patents and literature sources (see Supplementary material). The 31 inactive compounds consisted of compounds which do act as agonists for GPR119 at concentrations up to 10 µM, which we experimentally confirmed using our established HTRF assay [16]. These inactive chemicals consisted of compounds originating from three distinct chemical libraries (FDA, NIH clinical collection, Tocriscreen) ensuring structural diversity (see Supplementary material).…”
Section: Resultsmentioning
confidence: 96%
“…The inactive data set (See Supplementary Material) consisted of compounds determined not to activate GPR119 (less than 10 % of AR231453 activity) at a concentration of 10 µM. Previously, we have validated a high throughput cAMP assay for screening GPR119 ligands [16]. Using this assay, in the current study, we experimentally tested the compounds in three commercially available libraries (FDA-approved drug library, NIH clinical collection, and Tocriscreen) as potential GPR119 agonists.…”
Section: Methodsmentioning
confidence: 99%
“…SAR studies are of utmost importance for drug discovery in order to determine the important structural features required for higher pharmacological activities (Kumar et al, 2014;Singhuber et al, 2011).…”
Section: Discussionmentioning
confidence: 99%